NATURAL RESOURCE RENTAL INCOME AND R&D INTENSITY - Dipietro, William (Archives of Business Research, 2015)
The ease of obtaining rental income for countries with abundant natural resources having substantial world demand may lead to a diminutionin the pursuit of other forms of income such as income obtained from investing in research and development. If this proves to be the case, then it can have profound negative consequences for economic growth. In this light, this paper employs cross country regression analysis to test to see whether a greater share of natural resource rental income in national income is unfavorable for country R&D Intensity. Analyzing data for 2010 for a fairly substantial set of countries, the findings of the paper lend credence to the hypothesis that R&D intensity is negatively related to the size of the share of natural resource rental income relative to total income. This suggests that countries endowed with natural resourcesthat generate high levels of rental income must be very diligent in order to avoid the potentialnegative ramifications of rental income on their economic development.